Cardiovascular Disease Risk Following a 758 km Pilgrimage - Harris, M. B.; Wolf, M. R. (International Journal of Sports Medicine, 2013)
Millions of people participate in pilgrimages around the world such as the Camino de Santiago. However, few studies have examined the effects of this type of activity on cardiovascular disease risk factors. The aim of this study is to evaluate changes in cardiovascular disease risk factors: c-reactive protein, cholesterol, triglycerides, blood pressure, and cardiorespiratory fitness levels following a 758 km, 30-day pilgrimage. 11 healthy male and female subjects between the ages of 18–56 participated in pre and post pilgrimage blood pressure and blood tests, as well as pre, during, and post pilgrimage weight, skin-fold, and aerobic fitness testing. Heart rate monitors and pedometers provided maximum, average, and minimum heart rates as well as distances covered during the exercise. The mean daily walking distance was 25 km at an average intensity of 55.96% (±1.93%) of maximum heart rate. Statistically significant changes were seen in body weight (79.3 kg±3.4 pre vs. 76.4±2.98 post, p<0.05), body fat percentage (24.48%±2.31% pre vs. 23.01%±2.12 post, p<0.05), systolic and diastolic blood pressure (119±3.82/75±2.73 pre vs. 110±5.07/69±3.10 post, p<0.05), as well as cardiorespiratory fitness. These data suggest that some cardiovascular disease risk factors can be improved in healthy subjects participating in a low intensity, long duration, high frequency activity such as a walking pilgrimage.
Keywords: exercise; risk factors; Camino de Santiago; cardiovascular